Thought Leader Perspectives on Participant Protections in Precision Medicine Research - Hammack, Catherine M.; Brelsford, Kathleen M.; Beskow, Laura M. (The Journal of law, medicine & ethics, 2019)
Precision medicine research is rapidly taking a lead role in the pursuit of new ways to improve health and prevent disease, but also presents new challenges for protecting human subjects. The extent to which the current “web” of legal protections, including technical data security measures, as well as measures to restrict access or prevent misuse of research data, will protect participants in this context remains largely unknown. Understanding the strength, usefulness, and limitations of this constellation of laws, regulations, and procedures is critical to ensuring not only that participants are protected, but also that their participation decisions are accurately informed. To address these gaps, we conducted in-depth interviews with a diverse group of 60 thought-leaders to explore their perspectives on the protections associated with precision medicine research.